Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2011
DOI: 10.3109/07420528.2011.615182
|View full text |Cite
|
Sign up to set email alerts
|

Clock Gene Expression Levels and Relationship With Clinical and Pathological Features in Colorectal Cancer Patients

Abstract: The clock gene machinery controls cellular metabolism, proliferation, and key functions, such as DNA damage recognition and repair. Dysfunction of the circadian clock is involved in tumorigenesis, and altered expression of some clock genes has been found in cancer patients. The aim of this study was to evaluate the expression levels of core clock genes in colorectal cancer (CRC). Quantitative real-time polymerase chain reaction (qPCR) was used to examine ARNTL1, CLOCK, PER1, PER2, PER3, CRY1, CRY2, Timeless (T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
125
0
3

Year Published

2012
2012
2020
2020

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 127 publications
(138 citation statements)
references
References 63 publications
7
125
0
3
Order By: Relevance
“…While altered expressions of TIMELESS and DLX1 have been reported for a variety of cancers,2021222324 they have not been associated with prostate cancer metastasis. The elevated expression of TIMELESS found in our metastatic xenografts ( Table 1 ), as well as in metastatic prostate cancer patients’ samples (MSKCC cohort; Figure 2a ) and a strong correlation between elevated TIMELESS expression and poor clinical patients’ outcome (increased seminal vesicle invasion and lymph node involvement; Figure 2b ), suggest that this gene has a role in prostate cancer metastasis and perhaps as a metastasis-driving gene.…”
Section: Discussionmentioning
confidence: 89%
“…While altered expressions of TIMELESS and DLX1 have been reported for a variety of cancers,2021222324 they have not been associated with prostate cancer metastasis. The elevated expression of TIMELESS found in our metastatic xenografts ( Table 1 ), as well as in metastatic prostate cancer patients’ samples (MSKCC cohort; Figure 2a ) and a strong correlation between elevated TIMELESS expression and poor clinical patients’ outcome (increased seminal vesicle invasion and lymph node involvement; Figure 2b ), suggest that this gene has a role in prostate cancer metastasis and perhaps as a metastasis-driving gene.…”
Section: Discussionmentioning
confidence: 89%
“…Some translational studies have explored the relationship between Bmal1 and the clinical features of patients with colorectal cancer. Previous reports have suggested that Bmal1 expression in colorectal cancer tissues is lower than that in matched healthy mucosa (44). In addition, the expression of Bmal1 and Per1 also correlates with liver metastasis and colorectal cancer outcomes (45).…”
Section: Discussionmentioning
confidence: 98%
“…These findings provide a mechanistic foundation for the delayed onset of tumorigenesis in clock-disrupted p53 mutant mice, giving a note of optimism in treating cancers associated with p53 mutation [37]. In humans, the expression level of TIM was higher in the tumor tissue of colorectal cancer patients, while the overexpression of the circadian clock gene BMAL1 increases sensitivity to oxaliplatin in patients with colorectal cancer [38,39]. Mazzoccoli evaluated chronodisruption in lung cancer; actually, he found that in patients with lung cancer, GH, IGF1, TRH, TSH, FT4, cortisol and IL2 values did not show rhythmic variation [40].…”
Section: Clock-work Dysfunction and Cancermentioning
confidence: 81%